3D Seismic Structural Study of Zubair Formation in Najaf-Karbala Area-Central Iraq - Abdul Majeed, Ahmed S.; Ali, Kamal K. (Iraqi Journal of Science, 2023)
The current study included interpretations of the three-dimensional seismic survey data of the Najaf-Karbala region, which was recently implemented by the Fifth Amphibious Seismic crew of the Oil Exploration Company for the period from 30/1/2016 to 13/10/2017. The total area planned to be covered by the three-dimensional survey program was about (3340 km ²). The Zubair reflector was picked, interpreted, and tracked within the region. The faults affecting this reflector were captured. The reflector’s temporal, velocity, and depth maps showed the presence of structural closure features in the southeast of the region and extensions to the structural noses to the northwest of the study area. The structural maps showed a general tendency towards the east and the presence of faults in the area extending towards the northwest-southeast.